PENGEMBANGAN MEDIA PEMBELAJARAN PADA MATERI "PANCASILA DALAM KEHIDUPANKU" MATA PELAJARAN PPKN - Yosep Hadika Hidayati; Rana Gustian Nugrahai; Kusman Rukmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on a need for the procurement of digital learning mediabased on applications. The study aims to develop learning media applications onAndroid as a learning media for PPKN for grade V of Elementary Schools (SD).This research is development research on a digital learning media by developing alearning application called SILAKU. The method used in this study is Researchand Development (R&D). Participants in this study were 26 male and femalestudents involving two elementary schools, grade V, Kawungluwuk StateElementary School and State Elementary School, both of which are in SumedangRegency. The research and development steps use the ADDIE model, namelyAnalysis, Design, Development, Implementation, and Evaluation. The softwareused to develop this learning media uses Canva and Smart Apps Creator (SAC).The data collection method used by researchers is by distributing studentresponse questionnaires as well as media expert validation and materialvalidation. The results of the distribution of student response questionnairesobtained a value of 92.3% while the material expert validator obtained a value of99.47% and the media expert validator 88.89%. Thus, the overall results of thedistribution of student response questionnaires and validation fall into thecategories of "very feasible" and "very valid"